Analisis Lingkungan Industri pada Pelaku Usaha Mikro di Hamzah Batik Yogyakarta - Sir Kalifatullah Ermaya (Coopetition : Jurnal Ilmiah Manajemen, 2023)
This research was conducted on 30 creative SMEs in Yogyakarta who supply their products to Hamzah Batik. The classification of the craftsmen are: snacks, traditional home decorations, aromatherapy oils, wood crafts, silver crafts, batik bags, batik shoes and sandals, batik fabrics, traditional herbs and herbs as well as luxury materials such as jars and paintings. The results show that by using descriptive statistical analysis of the industrial analysis model created by Porter, the "buyer power" dimension with the indicator "consumer bargaining power in determining product selling prices" has the highest score or the most influential when compared to other indicators. Meanwhile, the “intensity of competition” dimension with the indicator “industry concentration affecting business in creative industries” has the lowest score. However, all indicators are in the very high category, which means that all indicators have a very high influence on the success of creative MSMEs in Yogyakarta which supply their products to Hamzah Batik. With the increase in globalization and to increase national GDP, the authors suggest increasing the competitiveness of MSME creative products in Yogyakarta by expanding their market, such as exporting their products abroad.